Development of Indigenous Child-Initiated Pretend Play Assessment: Selection of play materials and administration - Dender, Alma; Stagnitti, K. (Wiley-Blackwell Publishing Asia, 2011)
Background: There is a need for culturally appropriate assessments for Australian Indigenous children. This article reports the selection of culturally appropriate and gender-neutral play materials, and changes in administration identified to develop further the Indigenous Child-Initiated Pretend Play Assessment (I-ChIPPA). Method: Twenty-three typically developing children aged four to six years from the Pilbara region in Western Australia participated in the study. Children were presented with four sets of play materials and frequency counts were recorded for each time the child used one of the play materials in a pretend play action. Twelve of the 23 children came to play in pairs. Results: Both boys and girls used the Pilbara toy set including the dark coloured dolls and Pilbara region animals, more frequently than the standardised play materials from the Child-Initiated Pretend Play Assessment (ChIPPA). Conclusion: This study reports the first steps in the development of the I-ChIPPA. Future development will include the refinement of the administration and scoring with pairs of children, and then validity testing the assessment.